Advertisements
Advertisements
Question
Using the Mathematical induction, show that for any natural number n ≥ 2,
`1/(1 + 2) + 1/(1 + 2 + 3) + 1/(1 +2 + 3 + 4) + .... + 1/(1 + 2 + 3 + ... + "n") = ("n" - 1)/("n" + 1)`
Solution
Let P(n) is the statement
`1/(1 + 2) + 1/(1 + 2 + 3) + 1/(1 + 2 + 3 + 4) + ... + 1/(1 + 2 + 3 + ... + "n") = ("n" - 1)/("n" + 1)`
Given n ≥ 2
L.H.S ⇒ P(2) = `1/(1 + 2) = 1/3`
R.H.S ⇒ P(2) = `(2 - 1)/(2 +1) = 1/3`
L.H.S = R.H.S ⇒ P(n) is true for n = 2
Assume that the given tatement is true for n = k
(i.e) `1/(1 + 2) + 1/(1 +2 + 3) + ... + 1/(1 + 2 + 3 + ... + "k") = ("k" - 1)/("k" + 1)` is true
To prove P(k + 1) is true
P(k + 1) = `"P"("k") + ("t"_("k" + 1))`
= `("k" - 1)/("k" + 1) + 1/(1 + 2 + ... + "k" + 1)`
= `("k" - 1)/("k" + 1) + 1/((("k" + 1)("k" + 2))/2)`
= `("k" - 1)/("k" + 1) + 2/(("k" + 1)("k" + 2))`
= `(("k" - 1)("k" + 2) + 2)/(("k" + 1)("k" + 2))`
= `("k"^2 - "k" + 2"k" - 2 + 2)/(("k" + 1)("k" + 2))`
= `("k"^2 + "k")/(("k" + 1)("k" + 2))`
= `("k"("k" + 1))/(("k" + 1)("k" + 2))`
= `"k"/("k" + 1)^2`
= `("k" + 1 - 1)/("k" + 1 + 1)`
⇒ P(k + 1) is true when P(k) is true so by the principle of mathematical induction P(n) is true for n ≥ 2.
APPEARS IN
RELATED QUESTIONS
By the principle of mathematical induction, prove the following:
13 + 23 + 33 + ….. + n3 = `("n"^2("n + 1")^2)/4` for all x ∈ N.
By the principle of mathematical induction, prove the following:
4 + 8 + 12 + ……. + 4n = 2n(n + 1), for all n ∈ N.
By the principle of mathematical induction, prove the following:
32n – 1 is divisible by 8, for all n ∈ N.
By the principle of mathematical induction, prove the following:
an – bn is divisible by a – b, for all n ∈ N.
By the principle of mathematical induction, prove the following:
52n – 1 is divisible by 24, for all n ∈ N.
By the principle of mathematical induction, prove the following:
n(n + 1) (n + 2) is divisible by 6, for all n ∈ N.
The term containing x3 in the expansion of (x – 2y)7 is:
By the principle of mathematical induction, prove that, for n ≥ 1
13 + 23 + 33 + ... + n3 = `(("n"("n" + 1))/2)^2`
By the principle of mathematical induction, prove that, for n ≥ 1
12 + 32 + 52 + ... + (2n − 1)2 = `("n"(2"n" - 1)(2"n" + 1))/3`
By the principle of Mathematical induction, prove that, for n ≥ 1
1.2 + 2.3 + 3.4 + ... + n.(n + 1) = `("n"("n" + 1)("n" + 2))/3`
Using the Mathematical induction, show that for any natural number n ≥ 2,
`(1 - 1/2^2)(1 - 1/3^2)(1 - 1/4^2) ... (1 - 1/"n"^2) = ("n" + 1)/2`
Prove by Mathematical Induction that
1! + (2 × 2!) + (3 × 3!) + ... + (n × n!) = (n + 1)! − 1
Using the Mathematical induction, show that for any natural number n, x2n − y2n is divisible by x + y
By the principle of Mathematical induction, prove that, for n ≥ 1
`1^2 + 2^2 + 3^2 + ... + "n"^2 > "n"^2/3`
Use induction to prove that 5n+1 + 4 × 6n when divided by 20 leaves a remainder 9, for all natural numbers n
Choose the correct alternative:
If `""^("a"^2 - "a")"C"_2 = ""^("a"^2 - "a")"C"_4` then the value of a is
Choose the correct alternative:
1 + 3 + 5 + 7 + · · · + 17 is equal to